Upaya Meningkatkan Kreativitas dan Minat Belajar Anak di Kelurahan Sudiroprajan - Ahmad Firjatullah, Fikri Nur; Wati, Nori Laras; Martandang, Lailatul Bilkisa Putri; Adiba Al Adawi, Habibah Amalia Rosa; Afifah, Nida Nur; Rizkhy Pratama, Dhimas; Maharani, Galuh; Christina Manurung, Gita; Nur Azizah, Juwita; Kurnia Oktaviani, Leny; Adi Kurniawan, Dadan (Society : Jurnal Pengabdian Masyarakat, 2023)
In fact, there are still many children who have low creativity and interest in learning. There are PAUD schools that do not pay attention to their suitability in terms of buildings, educational resources, and there are elementary/middle school age children who prefer to spend time in one place playing games rather than studying together. KKN activities were carried out in Sudiroprajan Village, Jebres, Surakarta, Central Java. The methods used in this service are observation, socialization, mentoring and evaluation methods. As a result of observation and interview activities, problems were found to be provided for solutions through several work programs, namely literacy and numeracy through play activities, clean and healthy living education activities, coloring and drawing competitions, and study guidance. literacy and Numeracy through Play Activities improve literacy and numeracy skills. PHBS activities attract the interest of Cempaka PAUD children to maintain cleanliness and health. Drawing and coloring competition activities to develop the creativity of children in Sudiroprajan Village. Tutoring so that Sudiroprajan's children are enthusiastic about learning, as well as helping children who have learning difficulties. KKN 37 FKIP in Sudiroprajan Village has succeeded in providing a significant positive impact in developing the potential and quality of life of children in the area. Through various initiatives such as literacy and numeracy through play activities, PHBS counseling, drawing and coloring competitions, and tutoring, KKN students have made significant contributions in terms of children's education, health, creativity and learning motivation.